Multiomics analyses reveal high yield-related genes in the hypothalamic-pituitary-ovarian/liver axis of chicken - Jun’an Shi; Hanlin Xiong; Junchao Su; Qigui Wang; Haiwei Wang; Chaowu Yang; Chenming Hu; Zhifu Cui; Lingbin Liu (Poultry Science)
ABSTRACT: Egg production, regulated by multiple tissues, is among the most important economic traits in poultry. However, current research only focuses on the hypothalamic-pituitary-ovarian axis, ignoring the most important organ for substance metabolism in the body, the liver. Eggs are rich in lipids, proteins, and other nutrients, which are biosynthesized in the liver. Therefore, here the liver was included in the study of the hypothalamic-pituitary axis. This study used hypothalamus (HH_vs_LH), pituitary (HP_vs_LP), liver (HL_vs_LL), and ovary (HO_vs_LO) tissue samples from high- and low-laying Chengkou mountain chickens (CMC) for epihistological, transcriptome and metabolomic analyses aimed at improving the reproductive performance of CMC. The results showed that the liver of the high-laying group was yellowish, the cell boundary was clear, and the lipid droplets were evenly distributed. The ovaries of the high-laying group had a complete sequence of hierarchical follicles, which were rich in yolk. In contrast, the ovaries of the low-laying group were atrophic, except for a few small yellow follicles, and numerous primordial follicles that remained. The transcriptome sequences yielded 167.11 Gb of clean data, containing 28,715 genes. Furthermore, 285, 822, 787, and 1,183 differentially expressed genes (DEG) were identified in HH_vs_LH, HP_vs_LP, HL_vs_LL and HO_vs_LO and the DEGs significantly enriched 77, 163, 170, 171 pathways, respectively. Metabolome sequencing yielded 21,808 peaks containing 4,006 metabolites. The differential metabolite analysis yielded 343 and 682 significantly different metabolites (SDM) that significantly enriched 136 and 87 pathways in the liver and ovaries, respectively. A combined analysis of the transcriptome and metabolome of the liver and ovaries identified “CYP51A1-4α-carboxy-stigmasta7, 24(24(1))-dien-3β-ol” and “ACSS1B-estrone 3-sulfate” and other multiple gene-metabolite pairs. The DEGs in the hypothalamus and pituitary mainly enriched signaling transduction. In contrast, the DEGs and SDMs in the liver and ovaries mainly enriched the substance metabolism pathways: “gap junction”, “extracellular matrix (ECM)-receptor interaction”, “Steroid biosynthesis”, and “Steroid hormone biosynthesis”. These results suggest that the hypothalamic-pituitary axis may affect egg production mainly by regulating lipid metabolism in the liver and ovaries.